El método Delphi aplicado al estudio de la contribución de las TICs en la reducción de la pobreza en Andalucía - Carolina Ramírez; Julio García del Junco; Daniel Cejudo Reina (Atlantic Review of Economics (ARoEc), 2018)
– Poverty in Andalusia (sout hern region of Spain wit h a population of 8.411.205 inhabitants) affects 12,8% of its population. In this cont ext, the objective of this paper is to propose ways of reducing this situation of poverty extracted from various questionnaires to experts in the subject, following the Delphi Method. To achieve this objective, first of all, a de scription of the poverty data in Andalusia compared to Spain is provided; t he level of use of information and communication technologies in Andal usian households is deepened; the theoretical foundations of the Delphi method are devel oped to finally apply the Delphi method to the proposal of ways for the reduction of poverty in Andalusia and for the labor incorporation of Andal usian university students. The experts conclude that it would be necessary to create APPs for the information and training of potential worker s and entrepreneurs, both from the private and from the public spheres. They also highlight the need to make use of social networks with an orientation towards the employ ment relationship, encouraging the connection of companies and workers.
Keywords: I3; O14; 330